Teaching French in the Digital Age: A Sociological Examination of Teacher Professional Development and Technology Integration in the Classroom - Adaje , Mary Ebunoluwa; Adesope , John Adekunle (Interdisciplinary Journal Of Lifelong Learning, 2025)
This study examined Teaching French in the Digital Age: A Sociological Examination of Teacher Professional Development and Technology Integration in the Classroom among public junior secondary schools in Education District V, Lagos State. A descriptive survey design was adopted to analyse the relationship between teacher professional development and the integration of digital technology in French language instruction. The study population consisted of all French language teachers in the district, selected using a multi-stage sampling technique involving stratified and simple random sampling. Data were gathered from 80 respondents using a structured Likert-scale questionnaire, validated through expert review and pilot-tested for reliability, yielding a Cronbach Alpha coefficient of 0.83. Data were analysed using descriptive statistics, Pearson Product-Moment Correlation Coefficient (PPMCC), and an independent t-test. Results showed a moderate positive and significant relationship between teacher professional development and digital technology integration (r = 0.54, p < 0.05), while a significant effect of technology integration challenges on student engagement was also found (t = 2.31, p = 0.024). Conclusively, the study has established a significant relationship between teacher professional development and the integration of digital technology in the teaching of French in public junior secondary schools in Education District V, Lagos State. The findings revealed that as teachers receive more targeted training and professional development, their ability and confidence to integrate digital tools into classroom instruction improve markedly. It is recommended that Schools and educational authorities should prioritise ongoing professional development programmes that focus on the integration of digital tools in the classroom. For successful technology integration, schools must be equipped with the necessary ICT infrastructure, including reliable internet access, computers, and interactive digital tools.